Reductions in access to HIV prevention and care services are associated with arrest and convictions in a global survey of men who have sex with men. (4th March 2016) - Santos, Glenn-Milo; Makofane, Keletso; Arreola, Sonya; Do, Tri; Ayala, George
Abstract : Objectives: Men who have sex with men (MSM) are disproportionately impacted by HIV. Criminalisation of homosexuality may impede access to HIV services. We evaluated the effect of the enforcement of laws criminalising homosexuality on access to services. Methods: Using data from a 2012 global online survey that was published in a prior paper, we conducted a secondary analysis evaluating differences in perceived accessibility to health services (ie, 'how accessible are ____' services) between MSM who responded 'yes'/'no' to: 'have you ever been arrested or convicted for being gay/MSM?' Results: Of the 4020 participants who completed the study and were included in the analysis, 8% reported ever being arrested or convicted under laws relevant to being MSM. Arrests and convictions were most common in sub-Saharan Africa (23.6% (58/246)), Eastern Europe/Central Asia (18.1% (123/680)), the Caribbean (15% (15/100)), Middle East/North Africa (13.2% (10/76)) and Latin America (9.7% (58/599)). Those arrested or convicted had significantly lower access to sexually transmitted infection treatment (adjusted OR (aOR)=0.81; 95% CI 0.67 to 0.97), condoms (aOR=0.77; 95% CI 0.61 to 0.99) and medical care (aOR=0.70; 95% CI 0.54 to 0.90), compared with other MSM, while accounting for clustering by country and adjusting for age, HIV status, education and country-level income. Conclusions: Arrests and convictions under laws relevant to being MSM have a strong negative association with access to HIV prevention and care services. Creating an enabling legal and policy environment, and increasing efforts to mitigate antihomosexuality stigma to ensure equitable access to HIV services are needed, along with decriminalisation of homosexuality, to effectively address the public health needs of this population.